THE ROLE OF VITAMIN D IN PATHOGENESIS AND PREVENTION OF CARDIOVASCULAR DISEASES - A LITERATURE REVIEW - Natalia Jankowska,; Adrianna Świerzyńska,; Tomasz Puszkiel,; Aleksandra Simlat,; Aleksandra Cieciora,; Angelika Szwaj,; Ilona Mariańska-Wiśniewska,; Julia Surowiec,; Małgorzata Kawiorska,; Mateusz Cieciora, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Cardiovascular diseases remain the leading cause of mortality worldwide, and its incidence is increasing with the population aging. A growing number of studies indicate that vitamin D deficiency, which is common in the global population, may play an important role in the pathogenesis of cardiovascular diseases by influencing inflammatory processes, oxidative stress, the renin-angiotensin-aldosterone system, calcium-phosphate metabolism, and endothelial function. As a result, vitamin D has become the subject of intensive analysis regarding its potential impact on the prognosis of patients with hypertension, heart failure, atherosclerosis, diabetes, and arrhythmias.Aim of the study: The aim of the study was to present the current state of knowledge on the association between vitamin D deficiency and the risk and management of cardiovascular diseases, as well as to evaluate the role of vitamin D supplementation in the prevention and treatment of these diseases.Material and methods: This paper provides a review of the literature including current experimental, observational, and randomized controlled studies on vitamin D metabolism, the significance of 25(OH)D deficiency, pathophysiological mechanisms, and the effects of supplementation. Included publications present the impact of vitamin D on endothelial function, oxidative stress, atherosclerosis, the neurohormonal system, glucose metabolism, and the risk of arrhythmia.Results and Conclusions: A review of the literature indicates that vitamin D deficiency is associated with an increased risk of hypertension, heart failure, type 2 diabetes, atherosclerosis, and cardiac arrhythmias, including atrial fibrillation. The mechanisms of this effect include the action of VDR receptors in cardiomyocytes and vascular cells, modulation of the inflammatory response, reduction of oxidative stress, and regulation of the RAA system. Observational data suggest potential benefits of vitamin D supplementation, especially in high-risk groups, but large randomized clinical trials do not conclusively confirm that routine vitamin D administration reduces the number of major cardiovascular events in the general population. It is therefore necessary to individualize supplementation and conduct further well-designed studies to identify populations that may benefit most from therapy.